Nanostructured 2D MoS2 honeycomb and hierarchical 3D CdMoS4 marigold nanoflowers for hydrogen production under solar light - Kadam, Sunil R.; Late, Dattatray J.; Panmand, Rajendra P.; Kulkarni, Milind V.; Nikam, Latesh K.; Gosavi, Suresh W.; Park, Chan J.; Kale, Bharat B. (Journal of Materials Chemistry A, 2015)
Unique two dimensional (2D) honeycomb layered MoS2 nanostructures and hierarchical 3D marigold nanoflowers of CdMoS4 were designed using a template free and facile solvothermal method. The MoS2 structure is depicted with a sheet like morphology with lateral dimensions of 5-10 mu m and a thickness of similar to 200 nm and a honeycomb nanostructure architecture produced via the self-assembling of vertically grown thin hexagonal nanosheets with a thickness of 2-3 nm. The 3D CdMoS4 marigold nanoflower architecture comprised thin nanopetals with lateral dimensions of 1-2 mu m and a thickness of a few nm. The CdMoS4 and MoS2 structures displayed hydrogen ( H-2) production rates of 25 445 and 12 555 mu mol h(-1) g(-1), respectively. The apparent quantum yields of hydrogen production were observed to be 35.34% and 17.18% for CdMoS4 and MoS2, respectively. The 3D nanostructured marigold flowers of CdMoS4 and honeycomb like 2D nanostructure of MoS2 were responsible for higher photocatalytic activity due to inhibition of the charge carrier recombination. The prima facie observation of H-2 production showed that the ternary semiconductor confers enhanced photocatalytic activity for H-2 generation due to its unique structure. Such structures can be designed and implemented in other transition metal dichalcogenide based ternary materials for enhanced photocatalytic and other applications.